Evaluation of Counter Current Horizontal Screw Extractor’s Performance in Determining Leaching Equilibrium of Clitoria ternatea Anthocyanins - Ramadhani, Laily Isna; Hidayatulloh, Irwan; Nurcahyo; Trirahayu, Dhyna Analyes (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
Anthocyanin compounds as natural coloring substances contained in Clitoria ternatea flowers have higher antioxidant activity than anthocyanins from other flower extracts. Obtaining anthocyanin extract from Clitoria ternatea flower can be done using the solid-liquid extraction method. The objectives of this study include making a leaching equilibrium diagram of Clitoria ternatea flowers and determining the optimum L/S ratio and the number of equilibrium stages in the counter current horizontal screw extractor. In the maceration process, a leaching equilibrium diagram is produced, which is then used to design and determine the number of equilibrium stages. The equilibrium diagram of anthocyanins from Clitoria ternatea flowers with a gradient slope to the right is in accordance with the literature so that the equilibrium diagram can be used in the design of the extraction unit and the calculation of the theoretical stage of the multi-stage extraction unit. Based on the equilibrium diagram, the Number of Transfer Units (NTU) of 4 stages and the Height of the Transfer Unit value of this process is 0.105 m.